The Urban/Rural Community Divide Based on a Geo-Economic Perspective: An Analysis of Work Contracts in Slovakia - COLE DAVID; SVIDROŇOVÁ MÁRIA MURRAY; GUBALOVÁ JOLANA; STRNÁDOVÁ PETRA (Quaestiones Geographicae)
The study analyses over 1.5 million entries from the Slovak Social Insurance Company dataset for 2022. The records of work contracts for insured individuals are categorised by age, type of insurance, place of residence, and workplace, based on ZIP codes. By using ZIP codes, we were able to assess the connectivity of rural areas to workplaces, with a particular focus on the rural-urban divide. This approach highlights a geo-economic perspective in distinguishing urban and rural areas. Our analysis has revealed that most rural residents maintain strong urban economic connections, even extending to the capital city. Economically, only 26.6% of rural ZIP codes have more than 50% of their work contracts based within rural areas. Thus, we conclude that the term ‘rural’ carries more aesthetic than economic significance.